Development of A Virtual Laboratory for Electrochem to Support Students' Critical Thinking Skills - M Rizki; Rayandra Asyhar; Isra Miharti; Zurweni; Firdiawan Ekaputra (Universitas Pendidikan Mandalika, 2026)
The application of interactive learning media plays an important role in stimulating motivation and deepening students' understanding, especially in bridging the characteristics of abstract chemistry learning, one of which is the material of electrolyte and non-electrolyte solutions. The main problem in chemistry learning in Madrasah Aliyah is the limited physical laboratory facilities, which impacts the low critical thinking skills of students. This study aims to develop a Virtual Laboratory